ALGORITHM FOR ORGANIZING AND CONDUCTING A SUCCESSFUL INTEREST REPRESENTATION ADVOCACY CAMPAIGN - Lekholetova, Maryna; Liakh, Tetiana; Spirina Tеtiana (Social work and education, 2022)
Today, social advocacy is an effective tool for social change that influences attitudes, relations in the society, strengthens civil society, and contributes to the opening of democratic spaces for the implementation of best practices in social work and social equality. Social workers are aiming at helping people who are suffering from unemployment, violations of rights, difficult life circumstances, discrimination, etc. Thus social workers are in the constant process of individual work with vulnerable groups and often use interest representation as an intervention (protection of rights, representation of interests of individuals/groups of people to gain access to services, etc). The article analyzes several legal provisions that regulate advocacy, in particular, determining the basic rights of citizens and their associations. An algorithm for a successful advocacy campaign to represent the interests of vulnerable groups is proposed, which consists of eight stages (identification of social problems and goal setting, problem analysis, and goal setting, targeting, finding and identifying allies, identifying resources, creating a work plan, implementing a plan, monitoring and evaluation). The peculiarities and difficulties that may arise during the planning and implementation of the advocacy campaign are identified (weakness of the initiative group working on advocacy campaign planning; refusals and inaction of a certain "target" (representative of the authority)) advocacy team); too long campaign and, as a result, exhaustion of the initiative group; difficult confrontations of stakeholders who resist and have strong ties to the government; the unfavorable political situation for the social problem that needs to be solved; corruption schemes). Therefore, it is critical to focus on the systematic information component of the campaign (through constant communication with stakeholders), the availability of information to be conveyed to the target audience, be an attentive and timely response to arguments, and evidence of vulnerable groups affected by advocacy. It is emphasized that an important aspect of planning and implementing an advocacy campaign is to form a coalition and expand partnerships with other organizations that work in the context of a particular social problem or want to expand their activities.